Correlations between the somatic parameters and motor skills of 17-19-year-old boys from the Kujawsko-Pomorskie voivodeship - Mirosława Szark-Eckardt; Michalina Kuska; Hanna Żukowska; Małgorzata Pezala; Marek Napierała (Kazimierz Wielki University, 2018)
Abstract Introduction and purpose of the study: Physical activity is the key element of a healthy lifestyle. It is hard to associate it only with meeting the biological needs (Osiński, 1996). As hypokinesis is growing with age, it is becoming the cause of regress observed in physical fitness and efficiency of young generations (Woynarowska, 2008). The purpose of the study was to illustrate the condition of somatic development and motor skills in 17-19-year-old boys from the rural and urban areas of the Kujawsko-Pomorskie voivodeship. The correlations between the studied somatic characteristics and motor skills considering the age of respondents were identified using the Pearson correlation coefficient. Material and methods: The study involved 1,147 boys aged 17-19 years from the areas of the Kujawsko-Pomorskie voivodeship in 2015. The research was diagnostic and cross-sectional (transversal) in nature. The somatic parameters (body height and weight) were calculated in accordance with the guidelines adopted in anthropology whereas motor skills by means of MTSF. The correlations between the studied measurable parameters were identified by estimating the Pearson linear correlation coefficient. The study results were shown in the tabular and descriptive form. Results: The study revealed linear correlations between the somatic parameters and some motor skills in all age groups of boys (17-19 years). Conclusions: In order to establish the strategic directions for the changes concerning the condition of physical fitness, a detailed diagnosis of the current state is required that will help the school work of physical education teachers who can control different elements of biological development of their students in a better and more efficient way.